2010
DOI: 10.1007/s10704-010-9542-1
|View full text |Cite
|
Sign up to set email alerts
|

Two-parameter fracture criterion (K ρ,c -T ef,c ) based on notch fracture mechanics

Abstract: A two-parameter fracture criterion has been proposed to predict fracture conditions of notched components. This criterion includes the critical notch stress intensity factor K ρ,c , which represents fracture toughness of a material with a notch of radius ρ, and the effective T -stress. The effective T -stress T e f has been estimated as the average value of the T -stress distribution in the region ahead of the notch tip at the effective distance X e f . These parameters were derived from the volumetric method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Specimen geometry T-stress and associated transition temperature. For that purpose, it is necessary to obtain the "material master curve" which is the relationship between fracture toughness and constraint and effective T-stress (T ef ) at critical pressure for a test according to the procedure described in [13]. Unfortunately, these data are not yet available for X 65 and an estimation has been evaluated on the basis of the API 5L X52 pipe steel and a pipe diameter of 610 mm and thickness equal to 5.8 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Specimen geometry T-stress and associated transition temperature. For that purpose, it is necessary to obtain the "material master curve" which is the relationship between fracture toughness and constraint and effective T-stress (T ef ) at critical pressure for a test according to the procedure described in [13]. Unfortunately, these data are not yet available for X 65 and an estimation has been evaluated on the basis of the API 5L X52 pipe steel and a pipe diameter of 610 mm and thickness equal to 5.8 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Hadj Meliani et al [26] have also pointed out this effect on the notch fracture toughness K ρ ,c with the critical constraint T ef,c described by the critical value of the T ef,Xef parameter. The authors found a linear relationship between the two parameters:…”
Section: Background On Two-parameter Notch Fracture Resistancementioning
confidence: 93%
“…The shift in the stress distribution is introduced into the plastic constraint. In the literature, we can note the following constraint parameters: the plastic constraint factor [23], the stress triaxiality [24], the Q parameter [25], T stress [26] and A 2 [27].…”
Section: Background On Two-parameter Notch Fracture Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, the fracture conditions are considered not only at cracks tips, but also in some zones in the vicinity of flaws, taking into account stresses induced by crack surfaces interaction in these zones. Nonlocal fracture criteria, which can be used in these cases, have been intensively developed recently, see [4][5][6][7][8][9][10]. These criteria are based, as a rule, on two fracture conditions for the crack tip advancing (the stress and energy conditions in [4][5][6], the critical stress intensity and the T -stress in [7], and the finite fracture mechanics conditions in [8][9][10]), but they were implemented for cracks without consideration of large-scale process zone effects.…”
Section: Introductionmentioning
confidence: 99%